O13.1 Factors associated with safer sex efficacy among northern and indigenous youth in the northwest territories, canada. (14th July 2019) - Logie, Carmen; Lys, Candice; Mackay, Kayley; Macneill, Nancy; Pauchulo, Analaura; Yasseen, Abdool
Abstract : Background: Identifying social and structural factors associated with sexually transmitted infections (STI) vulnerability is urgent in the Northwest Territories (NWT), where STI prevalence is 7-fold the Canadian average. The NWT also experiences higher food insecurity and intimate partner violence (IPV) than the national average. Safer sex efficacy (SSE) comprises knowledge, intention, and relationship dynamics for safer sex negotiation. We examined social and structural factors associated with SSE among Northern and Indigenous adolescents in the NWT. Methods: With an Indigenous sexual health agency, we conducted a cross-sectional survey with adolescents aged 13–17 in 17 NWT communities. Summary statistics and statistical comparisons were conducted, followed by crude and multivariable regression models, with a canonical link function, to compare factors associated with SSE and within gender stratifications. We conducted post-hoc sensitivity analyses among Indigenous youth. Results: There were 610 participants (mean age: 14.2 years [SD: 1.5]; 49.5% cisgender women, 48.9% cisgender men, 1.6% transgender persons); three-quarters (n=447; 73.3%) were Indigenous. One-quarter (n=144; 23, 6%) reported food insecurity and nearly one-fifth (n=111; 18.2%) IPV. Among young women, food insecurity (β: -1.89[CI: -2.98, -0.80], p=0.001) and IPV (β: -1.31[CI: -2.53, -0.09], p=0.036) were associated with lower SSE in adjusted analyses, and currently dating was associated with increased SSSE (β: 1.17[CI: 0.15, 2.19], p=0.024). Among young men, food insecurity (β: -2.27[CI: -3.39, -1.15), p=0.014) was associated with reduced SSE. Among sexually active participants (n=115), increased SSE was associated with increased condom use among young women (β: 1.40[0.19, 2.61], p=0.024) and men (β: 2.14[0.14, 4.14], p=0.036). No differences emerged by Indigenous identity across analyses. Conclusion: Food insecurity and IPV emerged as syndemic factors associated with lower SSE—a protective factor associated with condom use among Northern and Indigenous adolescents in the NWT. Poverty and violence compromise Indigenous and Northern youth's sexual agency and in turn contribute to STI vulnerabilities, requiring urgent attention. Disclosure: No significant relationships.